2009
DOI: 10.1021/ct9003405
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Potential Derived Atomic Charges for Periodic Systems Using a Modified Error Functional

Abstract: A method to generate electrostatic potential (ESP) derived atomic charges in crystalline solids from periodic quantum mechanical calculations, termed the REPEAT method, is presented. Conventional ESP fitting procedures developed for molecular systems, in general, will not work for crystalline systems because the electrostatic potential in periodic systems is ill-defined up to a constant offset at each spatial position. In this work the problem is circumvented by introducing a new error functional which acts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
299
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(302 citation statements)
references
References 53 publications
2
299
0
1
Order By: Relevance
“…This shows that the ESP-derived charges do not reflect the change in the bond chemistry as the local coordination around a Ge or S atom varies. The REPEAT method [72], which is a corrected version of the ESP method developed for periodic systems, was also tested but nonphysical partial charges were obtained for both Ge and S atoms; indeed we obtained negative charges for many Ge atoms and positive charges for many S atoms. The failure of the REPEAT method [72] for chalcogenide materials has been already reported [72].…”
Section: A Electronic Density Of Statesmentioning
confidence: 97%
See 2 more Smart Citations
“…This shows that the ESP-derived charges do not reflect the change in the bond chemistry as the local coordination around a Ge or S atom varies. The REPEAT method [72], which is a corrected version of the ESP method developed for periodic systems, was also tested but nonphysical partial charges were obtained for both Ge and S atoms; indeed we obtained negative charges for many Ge atoms and positive charges for many S atoms. The failure of the REPEAT method [72] for chalcogenide materials has been already reported [72].…”
Section: A Electronic Density Of Statesmentioning
confidence: 97%
“…The REPEAT method [72], which is a corrected version of the ESP method developed for periodic systems, was also tested but nonphysical partial charges were obtained for both Ge and S atoms; indeed we obtained negative charges for many Ge atoms and positive charges for many S atoms. The failure of the REPEAT method [72] for chalcogenide materials has been already reported [72]. This is due to the fact that the ESP methodology cannot reproduce the electrostatic potential for systems with high local atomic densities [72].…”
Section: A Electronic Density Of Statesmentioning
confidence: 97%
See 1 more Smart Citation
“…. Point charges: Parameters can be obtained by minimising the difference of the classical electrostatic potential and a QM electrostatic potential over many grid points (ChelPG methods) [16 -18]; REPEAT method [19,20]; partial equalisation of orbital electronegativity (PEOE) or the Gasteiger method [21] and charge equilibration methods. [22 -24] .…”
Section: Force Fieldsmentioning
confidence: 99%
“…70 The authors noted that in the correspondence between HI and ESP fitted charges was found for a set of organic molecules. 47 We suspect that this is a deficiency inherent to the Hirshfeld-I procedure when applied to (nearly) ionic systems.…”
Section: Electrostatic Potentialmentioning
confidence: 99%